Statement by the Managing Director on the Work Program of the Executive Board Executive Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
This Work Program (WP) translates the strategic directions and policy priorities laid out in the Fall 2017 Global Policy Agenda (GPA) and the International Monetary and Financial Committee (IMFC) Communique into an Executive Board agenda for the next twelve months, with a focus on the next six months. The Managing Director's GPA, fully supported by the IMFC, called on members to take advantage of the window of opportunity from the more favorable conjuncture to tackle key policy challenges by undertaking well-sequenced reforms to increase productivity, reduce policy uncertainty and future risks, and improve governance. Reforms should also aim to harness the benefits of technology and economic integration and ensure that their benefits are widely shared. Tackling challenges to the global economy continues to require cooperation and joint action across the membership.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Policy; Policy Priority; Policy Uncertainty; Policy; PP